FEATURES OF THE PATHOGENESIS OF VISCERAL PAIN - V. G. Ovsyannikov; S. V. Shlyk; A. E. Boychenko; V. V. Alekseev; N. A. Alekseeva; O. A. Kaplunova (Медицинский вестник Юга России, 2013)
Peculiarities of visceral pain and its pathogenesis are analyzed in the article. The article presents role of receptor apparatus, which accepts algogenic information, conducting structures role of spinal cord and brain in the formation of visceral pain. The pain mediators, neurotransmitters of spinal cord, and the theory of referred pain are analyzed.